EFFECTS OF GRADED LEVELS OF Adansonia digitata (BAOBAB) LEAVES ON TESTICULAR MORPHOMETRY AND GONADAL SPERM RESERVE OF RED SOKOTO BUCKS - Ibrahim, Kabir; Stephen, Jashilagari; Sidi, Shehu; Mohammed, Aminu Umar; Jibril, Aliyu; Abubakar, Abubakar Umar; Adewale, Ayodeji Adeyeye (FUDMA Journal of Sciences, 2025)
This study was designed to evaluate the effects of graded levels of Adansonia digitata leaves on testicular morphometry and gonadal sperm reserve of Red Sokoto bucks (RSB). Twenty RSBS were randomly assigned to four groups (A, B, C and D) of five bucks. Group B, C, and D received graded levels of Adansonia digitata leaves powder in their diet for 14 weeks, while group A served as a control. Open castration was performed on eight (8) bucks (randomly selected, with two (2) from each group) at week fifteen (15). The RSB scrotal circumference, scrotal length, testicular volume, testicular width, and gonadal sperm reserves were evaluated. There was no significant difference (P > 0.05) in scrotal circumference, scrotal length, testicular volume, and testicular width in bucks fed with Adansonia digitata leaves and those in the control group throughout the study. A Significant (P < 0.05) difference in GSR between the groups was observed. This study, therefore, found a decrease in scrotal circumference, scrotal length, testicular volume, and testicular width, but with GSR improvement between their respective groups. It was concluded that feeding graded levels of Adansonia digitata leaves at 3, 6, and 9 g/h/day to RSB may compromise their scrotal circumference, scrotal length, testicular volume, and testicular width, but increase their gonadal sperm reserve, especially at 6g/h/day, which can improve their reproductive potential. Further studies on the effects of antioxidants from the Adansonia digitata leaves, such as vitamins A, C and E, on other testicular parameters are also recommended.